UPAYA PENINGKATAN PASSING BAWAH BOLA VOLI DENGAN PENDEKATAN BERMAIN DI SDN 13 MANGARO - Juwita, Blandina; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this research to improve learning outcomes under volleyball passing grade the students of SDN 13 Mangaro through play approach. The method used in this research is descriptive type of research is classroom action research). Subjects in this study were the students of SDN 13 Mangaro, amounting to 36 learners. The results of this study have shown a significant improvement for the development of learners. It can be seen on the first cycle students are the results of students who completed totaling 16 students or 44.4%, while students and who have not completed a total of 20 students, or by 55.6%, then proceed to the second cycle of improvement under the approach passing play with category complete all of the students passed the 36 students and unfinished amounted to 0 or does not exist.Keywords: Passing Down, Volleyball, Playing Approach